2022
DOI: 10.1002/anie.202206044
|View full text |Cite
|
Sign up to set email alerts
|

A Chain‐Growth Mechanism for Conjugated Polymer Synthesis Facilitated by Dinuclear Complexes with Redox‐Active Ligands

Abstract: Conjugated polymers are widely used in energy conversion and sensor applications, but their synthesis relies on imprecise step-growth or narrowscope chain-growth methods, typically based on transition metal (TM)-catalyzed cross-coupling. Here we report that a dinickel complex with a redox-active naphthyridine diimine ligand accesses new chain-growth mechanistic manifolds for both donor and acceptor conjugated polymers, represented by poly(3-hexylthiophene), poly(2,3-bis(2-ethylhexyl)thienopyrazine), and poly(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Alternatively, complexes with multiple metal centers can unlock new forms of reactivity and effectively expand the "toolbox" for chemical transformations�as evidenced by examples in both synthetic and biological systems. 9−12 Based on the findings from our previous work, 16 we sought a catalyst scaffold that (1) had a redox-active ligand, (2) placed the metals in proximity of each other, (3) formed complexes with multiple different first-row metals, and (4) could be readily compared to mononuclear analogs. We selected the bis(pyridine diimine) scaffold pioneered in the Tomson group because it fits these criteria and allowed us to investigate both nickel and iron complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alternatively, complexes with multiple metal centers can unlock new forms of reactivity and effectively expand the "toolbox" for chemical transformations�as evidenced by examples in both synthetic and biological systems. 9−12 Based on the findings from our previous work, 16 we sought a catalyst scaffold that (1) had a redox-active ligand, (2) placed the metals in proximity of each other, (3) formed complexes with multiple different first-row metals, and (4) could be readily compared to mononuclear analogs. We selected the bis(pyridine diimine) scaffold pioneered in the Tomson group because it fits these criteria and allowed us to investigate both nickel and iron complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The g-value of the chemically reduced P1 radical anion is 2.0035, and that of the reaction mixture is 2.0033, both of which are in agreement with the values for a dimer radical anion from a report by King and Zhukhovitskiy published after our original article. 1 The caption of Figure 2 has been corrected to reflect the revised procedure and data.…”
mentioning
confidence: 99%
“…Additionally, the gvalue we observed for doped P1 likely corresponds to trace metal-centered radical, not an organic radical anion. 1 We have since found that our original conditions for polymer reduction with sodium napththalenide did not sufficiently reduce P1. Instead, excess Na metal does reduce P1, which we confirmed with UV−vis absorption and spectroelectrochemistry (Figures S24 and S25, respectively, in the revised Supporting Information presented here).…”
mentioning
confidence: 99%
See 2 more Smart Citations